Politicisation of Religion in Pakistan: A Case Study on Ministry of Religious Affairs (MORA) - Sanghro, Rafi Raza (Journal of History Culture and Art Research, 2020)
Pakistan was created in the name of religion (Islam) as an independent country in 1947 on the basis of Two Nation Theory wherein the Muslims of Indian subcontinent could live, preach and profess their religion freely from the dominance of Hindus. After independence the state elites did not make any tangible programmes which could establish the country as an Islamic state. However, the state elites established religious ministry after 27 years of the establishment of Pakistan. The ministry was not established to implement or enforce religious programmes for Pakistan. Contrary it was established to control religious elites and their institutions which could be used for political gain. This paper is designed to illustrate the historical aspect of role of religion in Pakistan. The paper further will analyse how state elites used religion for political gains by politicising religion in Pakistan.